Dysfunction in Ribosomal Gene Expression in the Hypothalamus and Hippocampus following Chronic Social Defeat Stress in Male Mice as Revealed by RNA-Seq. (29th December 2015) - Smagin, Dmitry A.; Kovalenko, Irina L.; Galyamina, Anna G.; Bragin, Anatoly O.; Orlov, Yuriy L.; Kudryavtseva, Natalia N.
Abstract : Chronic social defeat stress leads to the development of anxiety- and depression-like states in male mice and is accompanied by numerous molecular changes in brain. The influence of 21-day period of social stress on ribosomal gene expression in five brain regions was studied using the RNA-Seq database. Most Rps, Rpl, Mprs, and Mprl genes were upregulated in the hypothalamus and downregulated in the hippocampus, which may indicate ribosomal dysfunction following chronic social defeat stress. There were no differentially expressed ribosomal genes in the ventral tegmental area, midbrain raphe nuclei, or striatum. This approach may be used to identify a pharmacological treatment of ribosome biogenesis abnormalities in the brain of patients with "ribosomopathies."